2011
DOI: 10.4314/njbas.v19i1.69359
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variety and Fungicidal Rate on <i>Cercospora</i> Leaf Spots Disease of Groundnut in the Sudan Savanna

Abstract: A field study was carried out at the University of Maiduguri Teaching and Research Farm during the 2006, 2007 and 2008 cropping seasons to evaluate the effects of variety and fungicidal rate on Cercospora leaf spot disease of groundnut. The experimental design used was Randomized Complete Block Design (RCBD) with twelve treatment combinations of three varieties of groundnut (Ex-Dakar, RRB and ICGV-86024) and four levels of fungicidal rate (0, 1, 2 and 4 kgha ¹ of fungicide mancozeb) replicated three times. Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…The highest disease reduction was found in Azadirachta indica after mancozeb. The findings for disease intensity are in agreement with the findings of Rajmachi et al (2012), Mushrif et al (2017), Hossain and Hossain (2013b) and Muhammad and Bdliya (2011). In spite of this, our results do not correlate with the findings of Mapari and Sunil (2016) and Hasan et al (2016) that D. metel showed better performance in their experiment.…”
Section: Efficacy Of Botanical Extracts On Disease Intensity Of Leaf Spot Of Groundnut At 80dassupporting
confidence: 80%
“…The highest disease reduction was found in Azadirachta indica after mancozeb. The findings for disease intensity are in agreement with the findings of Rajmachi et al (2012), Mushrif et al (2017), Hossain and Hossain (2013b) and Muhammad and Bdliya (2011). In spite of this, our results do not correlate with the findings of Mapari and Sunil (2016) and Hasan et al (2016) that D. metel showed better performance in their experiment.…”
Section: Efficacy Of Botanical Extracts On Disease Intensity Of Leaf Spot Of Groundnut At 80dassupporting
confidence: 80%
“…Four cultivars produced higher haulm yield and presented lower CLS severity. Also, Muhammad and Bdliya (2015) found significant differences in three groundnut genotypes and indicated that this could probably to be due to difference in the inherent resistance of the cultivars to attack by the fungus. In the other hand, Izge et al (2007) found four groundnut cultivars had lower levels of Cercospora leaf spot severity, suggesting that they were comparatively tolerant to CLS, but four cultivars were recognized as comparatively having higher disease severity consistently suggesting that they were susceptible to CLS.…”
Section: Resultsmentioning
confidence: 97%
“…These results were also in concurrence with Devi and Prasad (2009) who reported that combined effect of seed treatment with T. viride and captan resulted in significant reduction of collar rot and combination of antagonist and fungicide also improved the growth parameters like the length of the plant, biomass and yield besides decreasing the disease incidence. Muhammad and Bdliya (2011) evaluated the effects of variety and fungicide (mancozeb) on Cercospora leaf spot disease of peanut and found that disease incidence and disease severity were significantly higher in "ExDakar" variety and untreated seeds, thus had lower yields. Higher seed and haulm yield were recorded by RRB, ICGV-86024, as well as 2 and 4 kg ha -1 as a result of lower disease incidence and severity.…”
Section: The Following Treatments (Fungicides) Were Used As Seed Dresmentioning
confidence: 99%